Manajemen Pendidikan Multikultural Berbasis Dimensi James A. Banks: Studi Kasus Madrasah Diniyah Nurul Hidayah Nganjuk - Ana, Ana Imroatul Mufidata; Addin Arsyadana (LPTK UIN Syekh Wasil Kediri, 2025)
This study aims to explore the implementation of James A. Banks’ five dimensions of multicultural education in fostering harmony through effective management practices at Madrasah Diniyah Nurul Hidayah, Nganjuk. Using a qualitative field research design, data were collected through in-depth interviews, participant observation, and document analysis involving the school principal, teachers, students, and foundation administrators. The findings reveal that the institution has successfully integrated multicultural values through the four core functions of management, planning, organizing, actuating, and controlling, based on George R. Terry’s management theory. The study demonstrates that the dimensions of content integration, knowledge construction, prejudice reduction, equity pedagogy, and empowering school culture have been consistently applied, despite the institution's non-formal nature. These practices contribute significantly to creating a peaceful, respectful, and inclusive school environment, leading to both academic and non-academic achievements. The results highlight the relevance of multicultural education management as a practical strategy for promoting social harmony in diverse Islamic educational settings.